Attracting and retaining sports fans - Shields, Ben; Rein, Irving (Henry Stewart Talks, 2008)
Problems of attracting and retaining sports fans, Historical perspective on the causes of the contemporary fan attraction and retention challenge, Systematic approach to solving problems based on fan connections, brand transformation and strategy development, Specific discussion of the essential strategies for fan engagement
Archived at 2022/04/04